Identification of the centrosomal maturation factor SSX2IP as a Wtip-binding partner by targeted proximity biotinylation - Alice H. Reis; Bo Xiang; Olga Ossipova; Keiji Itoh; Sergei Y. Sokol (PLoS ONE, 2021)
Wilms tumor-1-interacting protein (Wtip) is a LIM-domain-containing adaptor that links cell junctions with actomyosin complexes and modulates actomyosin contractility and ciliogenesis in Xenopus embryos. The Wtip C-terminus with three LIM domains associates with the actin-binding protein Shroom3 and modulates Shroom3-induced apical constriction in ectoderm cells. By contrast, the N-terminal domain localizes to apical junctions in the ectoderm and basal bodies in skin multiciliated cells, but its interacting partners remain largely unknown. Targeted proximity biotinylation (TPB) using anti-GFP antibody fused to the biotin ligase BirA identified SSX2IP as a candidate protein that binds GFP-WtipN. SSX2IP, also known as Msd1 or ADIP, is a component of cell junctions, centriolar satellite protein and a targeting factor for ciliary membrane proteins. WtipN physically associated with SSX2IP and the two proteins readily formed mixed aggregates in overexpressing cells. By contrast, we observed only partial colocalization of full length Wtip and SSX2IP, suggesting that Wtip adopts a ‘closed’ conformation in the cell. Furthermore, the double depletion of Wtip and SSX2IP in early embryos uncovered the functional interaction of the two proteins during neural tube closure. Our results suggest that the association of SSX2IP and Wtip is essential for cell junction remodeling and morphogenetic processes that accompany neurulation. We propose that TPB can be a general approach that is applicable to other GFP-tagged proteins.